2020
DOI: 10.1126/sciadv.aax3868
|View full text |Cite
|
Sign up to set email alerts
|

The RNA binding protein CPEB2 regulates hormone sensing in mammary gland development and luminal breast cancer

Abstract: Organogenesis is directed by coordinated cell proliferation and differentiation programs. The hierarchical networks of transcription factors driving mammary gland development and function have been widely studied. However, the contribution of posttranscriptional gene expression reprogramming remains largely unexplored. The 3′ untranslated regions of messenger RNAs (mRNAs) contain combinatorial ensembles of cis-regulatory elements that define transcript-specific regulation of protein synthesis through their cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…CPEB2 elongates the poly(A) tail length of CPE-containing mRNAs, regulating post-transcriptionally mRNAs downstream of steroid hormone signaling, emphasizing the importance of this regulatory molecule in the development of luminal A subtype. Published data from CPEB2 RNA immunoprecipitation [ 22 ] identified 169 mRNAs co-immunoprecipitated with CPEB2 in mammary epithelial cells. We identified 41 of these molecules, also present in LINC00504 co-expression network ( Supplementary Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CPEB2 elongates the poly(A) tail length of CPE-containing mRNAs, regulating post-transcriptionally mRNAs downstream of steroid hormone signaling, emphasizing the importance of this regulatory molecule in the development of luminal A subtype. Published data from CPEB2 RNA immunoprecipitation [ 22 ] identified 169 mRNAs co-immunoprecipitated with CPEB2 in mammary epithelial cells. We identified 41 of these molecules, also present in LINC00504 co-expression network ( Supplementary Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…CPEB2 regulates the poly(A) tail length of CPE-containing mRNAs, contributing to mammary gland development and luminal breast carcinogenesis by regulating the translation of mRNAs downstream of steroid hormone signaling [ 22 ]. Pascual et al 2020 [ 22 ], using METABRIC and TCGA breast cohorts, verified that CPEB2 is associated with ESR1 levels, and high levels of CPEB2 were associated with worse survival compared to samples with the lowest expression in luminal A patients. On the other hand, ER − tumors (such as basal-like) do not seem to require CPEB2 ; low levels of CPEB2 result in reduced survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evasion of immune destruction of cancer cells is one key hallmark of cancer ( Hanahan and Weinberg, 2011 ), and RBPs can regulate the function and activity of immune cells, which eventually may be linked to immune surveillance evasion of cancer cells through managing the RNA metabolism at the post-transcription level ( Kafasla et al, 2014 ; Pereira et al, 2017 ). In addition, accumulating studies have reported that dysregulated expression of RBP-facilitated cell proliferation, invasion, and metastasis and pluripotency and stemness in multiple cancers ( Yu et al, 2007 ; Dong et al, 2019 ; Soni et al, 2019 ; Velasco et al, 2019 ; Elcheva et al, 2020 ; Pascual et al, 2020 ). However, few studies have analyzed the expression patterns and roles of RBPs in SCCHN.…”
Section: Discussionmentioning
confidence: 99%
“…Evasion of immune destruction of cancer cells is one key hallmark of cancer (Hanahan and Weinberg, 2011), and RBPs can regulate the function and activity of immune cells, which eventually may be linked to immune surveillance evasion of cancer cells through managing the RNA metabolism at the post-transcription level (Kafasla et al, 2014;Pereira et al, 2017). In addition, accumulating studies have reported that dysregulated expression of RBP-facilitated cell proliferation, invasion, and metastasis and pluripotency and stemness in multiple cancers (Yu et al, 2007;Dong et al, 2019;Soni et al, 2019;Velasco et al, 2019;Elcheva et al, 2020;Pascual et al, 2020). However, few studies have analyzed the expression patterns and roles of RBPs in SCCHN.…”
Section: Discussionmentioning
confidence: 99%